Microstructured titanium functionalized by naringin inserted multilayers for promoting osteogenesis and inhibiting osteoclastogenesis. Issue 14 (4th October 2021) - Shen, Ke; Zhang, Xiaojing; Tang, Qiang; Fang, Xingtang; Zhang, Chunlei; Zhu, Zhaojing; Hou, Yanhua; Lai, Min
Abstract: Osteoporosis is the most common cause of fractures in middle-aged and elderly people. Fracture repair can be difficult due to the decreased bone volume in osteoporosis patients and implants are often required. In this study, a slow-release system for microstructured titanium (Micro-Ti) was designed to promote osteogenesis and inhibit osteoclastogenesis. Firstly, Micro-Ti was prepared on titanium surfaces by dual acid etching. Micro-Ti was covered with naringin (NA), chitosan (CHI) and gelatin (GEL) multilayers through layer by layer technique, which is denoted as LBL (NA) coated-Ti. Osteoblasts (ME3T3-E1) and macrophages (RAW 264.7) were cultured on untreated and treated titanium surfaces in vitro . Osteoblasts grown on LBL (NA) coated-Ti showed higher alkaline phosphatase (ALP) and mineralization, consistent with qRT-PCR analysis of osteoblast genes including runt-related transcription factor 2 (Runx2), ALP, collagen I (Col I), osteocalcin (OCN), osteopontin (OPN), and osteoprotegerin (OPG). In contrast, acid tartarate-resistant phosphatase activity and the expression of osteoclastic differentiation related genes comprising of cathepsin K (CTSK), nuclear factor of activated T cells (NFAT), tartrate resistant acid phosphatase (TRAP) and V-ATPase (VATP) in osteoclasts were significantly reduced on LBL (NA) coated-Ti surfaces compared with other groups. These results indicate that microstructured titanium functionalized by naringin inserted multilayers enhanced the differentiation of osteoblasts and inhibited osteoclast formation. The proposed approach in this research provides a novel way to modify titanium-based implants for fracture repair in osteoporosis patients.